Theoretical Analysis and Quick Calculation of Spur Gear Tooth Deformation - Zhang Jingcai; Liu Hongqi; Zhao Xiangfei; Yang Chao (Jixie chuandong)
A quick calculation method of gear tooth deformation based on mechanics of materials,and calculation formulas for each deformation are analyzed and demonstrated. A modified gear tooth basic deformation Weber- Banaschck formula is proposed. The result coinciding with ISO is achieved. The characteristic and rule of gear tooth contact,bending,shear,compress and basic deformation and so on are analyzed with a gear tooth form factor without unit. A method to approximate gear deformation curve with parabolic which defined by minimum deformation δ0,deformation at right and left side δRand δL. It has a high accuracy and a basic for analyzing of gear transmission error changing and simple calculating of gear tooth modification curve is provided.